2009
DOI: 10.1590/s0100-204x2009000800031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between macrofauna, mineralogy and exchangeable calcium and magnesium in Cerrado Oxisols under pasture

Abstract: -The objective of this work was to assess the relationship between macrofauna, mineralogy and exchangeable calcium and magnesium in Cerrado Oxisols under pasture. Twelve collection points were chosen in the Distrito Federal and in Formosa municipality, Goiás state, Brazil, representing four soil groups with varied levels of calcium + magnesium and kaolinite/(kaolinite + gibbsite) ratios. Soil macrofauna was collected in triplicate at each collection point, and identifi ed at the level of taxonomic groups. Macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
3
0
2
Order By: Relevance
“…However, the diversity of macro fauna groups was negatively affected by Calcium levels, and this may explain why mixed cropping was the least in terms of macro fauna diversity. This is in line with findings of [8], who verified that both mineralogy and levels of exchangeable Calcium have a significant effect on the diversity of soil macro fauna at the order level. In their study, results suggested that the chemical and mineralogical characteristics of soils are important variables explaining the abundance and diversity of macro fauna in Oxisols under pasture use in Cerrado.…”
Section: Discussion:-supporting
confidence: 92%
“…However, the diversity of macro fauna groups was negatively affected by Calcium levels, and this may explain why mixed cropping was the least in terms of macro fauna diversity. This is in line with findings of [8], who verified that both mineralogy and levels of exchangeable Calcium have a significant effect on the diversity of soil macro fauna at the order level. In their study, results suggested that the chemical and mineralogical characteristics of soils are important variables explaining the abundance and diversity of macro fauna in Oxisols under pasture use in Cerrado.…”
Section: Discussion:-supporting
confidence: 92%
“…Esse resultado contrasta com relatos no Sul do país, onde a abundância e a riqueza de minhocas não diferem entre áreas de floresta e de plantio direto, e podem ser utilizadas como indicadora da qualidade do solo (Bartz et al, 2013). Em estudos em outras regiões de Cerrado, o grupo Oligochaeta pode figurar, até mesmo entre um dos quatro mais abundantes (Santos et al, 2008;Marchão et al, 2009;Vendrame et al, 2009). No Piauí, contudo, as minhocas ainda não haviam sido amostradas até 2007 (Brown et al, 2006).…”
Section: Resultsunclassified
“…As famílias Rhinotermitidae e Termitidae não apresentaram correlação significativa com Ca. Vendrame et al (2009) Salton et al, 2008), favorecendo distúrbios ou equilíbrio no ambiente do solo.…”
Section: Local Os Autores Verificaram Maior Densidade Deunclassified